Catalytic cracking catalyst as well as preparation method and application thereof

By combining modified ZSM-5 molecular sieve and Y-type molecular sieve, the coordinated modification of titanium source and phosphorus source is used to solve the problems of waste liquid treatment of titanium-based polypropylene catalyst and the thermal stability of ZSM-5 molecular sieve, achieving the effect of efficient conversion of heavy oil and high yield of low-carbon olefins during catalytic cracking.

CN119909722AActive Publication Date: 2025-05-02PETROCHINA CO LTD

Patent Information

Application Number
CN202311423266.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02
Estimated Expiration
2043-10-30

AI Technical Summary

Technical Problem

In the prior art, the waste liquid containing titanium tetrachloride generated during the preparation of titanium polypropylene catalyst is inconvenient to treat, resulting in environmental pollution and waste of resources. At the same time, the thermal stability of ZSM-5 molecular sieve is not high, affecting its application in the catalytic cracking process.

Method used

The catalyst component A and catalyst component B composed of modified ZSM-5 molecular sieve and Y-type molecular sieve are used to improve the acidic distribution and hydrothermal stability of ZSM-5 molecular sieve through the coordinated modification of the titanium source and the phosphorus source, and use waste liquid containing titanium tetrachloride as a modifier to reduce the waste liquid treatment cost.

Benefits of technology

The efficient conversion of heavy oil during catalytic cracking is achieved, which reduces the yield of heavy oil and coking tendency, while improving the yield of low-carbon olefins and aromatics, and improving the thermal stability and wear resistance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909722A_ABST
    Figure CN119909722A_ABST
Patent Text Reader

Abstract

The invention provides a catalytic cracking catalyst as well as a preparation method and application thereof. The catalytic cracking catalyst comprises a catalyst component A and a catalyst component B in a weight ratio of 98: 2-20: 80, the catalyst component A comprises the following raw materials: 15-55% of a modified ZSM-5 molecular sieve, 10-55% of clay, 3-20% of an aluminum source and 5-20% of phosphorus from a second modifier; the modified ZSM-5 molecular sieve is obtained by modifying a raw material ZSM-5 molecular sieve by using a first modifier; the first modifier comprises a titanium source and a phosphorus source; and the component B of the catalyst comprises the following raw materials: 15-50% of a Y-type molecular sieve, 10-55% of clay, 5-30% of pseudo-boehmite, 3-20% of a binder and 0-5% of a modified metal element. The invention also provides a preparation method of the catalytic cracking catalyst and application of the catalytic cracking catalyst in a catalytic cracking process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oil refining catalysts and additives, and in particular to a catalytic cracking catalyst and a preparation method and application thereof. Background Art

[0002] In the process of industrial production of polyolefins, the widely used catalyst is mainly Ziegler-Natta catalyst, which is a titanium catalyst. Regarding the preparation of titanium polyolefin catalysts, for example, Chinese patent CN 102336851A discloses a propylene polymerization catalyst, including magnesium, titanium, halogen and internal electron donor compounds diisobutyl phthalate, diethyl phthalate or di-n-butyl phthalate and a mixture of succinate; Chinese patent CN 107434832 B discloses a propylene polymerization catalyst, mainly composed of an alcohol magnesium compound, a titanium compound and a phosphate electron donor compound. The common method for preparing titanium catalysts at present is: first, the preparation of magnesium halide alcoholate is carried out, for example, after the magnesium halide and alcohol are heated and dissolved, high pressure ejection or high-speed stirring is used, and the method of solidifying into microsphere particles in a cooling medium is obtained, and the specific steps are referred to the relevant description in CN1110281A; then the magnesium halide alcoholate particles are reacted with a halogen-containing compound such as titanium tetrachloride to prepare a magnesium-supported catalyst, during which various promoters can be added for modification. In the above-mentioned catalyst preparation process, a large amount of titanium tetrachloride needs to be used, and the excess ratio is very large. At the same time, the obtained solid catalyst component needs to be washed with a hydrocarbon solvent (such as hexane) to remove the unloaded titanium tetrachloride therein. Therefore, in the polyolefin catalyst production process, after the catalyst solid is separated and precipitated, a large amount of catalyst mother liquid containing at least one of titanium tetrachloride, unreacted hydrocarbons, unreacted halogenated alkoxy titanium, alkoxy magnesium, and unreacted esters will be produced. A large amount of waste liquid containing titanium tetrachloride is produced in the titanium-based polypropylene catalyst preparation process, wherein the titanium tetrachloride content is about 80%-95% (by weight), which is bound to cause environmental pollution and waste of resources if discharged into the environment. At present, there is a lack of simple and effective methods for recycling and treating waste liquid containing titanium tetrachloride and reducing environmental pollution. In addition, the thermal stability of the existing ZSM-5 molecular sieve is not high. Even after modification by known methods, the thermal stability of the ZSM-5 molecular sieve is still not ideal, which is not conducive to the use of the molecular sieve, especially the application of the molecular sieve as a cracking catalyst. In the prior art, for example, Chinese patent CN102114429 B discloses a method for increasing the B acid content of ZSM-5 molecular sieve and achieving increased production of light olefins, which is to modify the ZSM-5 molecular sieve with iron and titanium at the same time, and the mass ratio of iron to titanium in the modified molecular sieve is 0.3-3:1, so that the catalytic reactivity of the molecular sieve is improved, and the conversion of long-chain alkanes and aromatic hydrocarbons with long-chain alkyl side chains such as isopropylbenzene is promoted, so as to achieve the effect of increasing the yield of light olefins. U.S. Patent US5171921 discloses a method for modifying ZSM-5 molecular sieve, which includes exchanging the synthesized ZSM-5 molecular sieve with ammonium to reduce sodium, drying, and roasting, and then modifying with phosphoric acid, drying, and roasting to obtain a phosphorus-containing ZSM-5 molecular sieve.

[0003] In addition, the adverse effects of high heavy oil yield, high coke production and low light olefin yield in the catalytic cracking catalyst prepared by the prior art also need to be overcome. In the prior art, for example, Chinese patent CN 101898146 B discloses a catalytic thermal cracking catalyst and a preparation method thereof, wherein the catalyst contains 5-75% by weight of an aluminum binder in terms of alumina, 0.5-70% by weight of a zeolite with an MFI structure, and 3-25% by weight of a zirconium oxide matrix, wherein the silicon-aluminum ratio of the zeolite with an MFI structure is 15-300, and the primary particle diameter is 5-55 μm. The catalyst preparation method includes the steps of mixing and slurrying the zeolite with an MFI structure with an alumina binder and a zirconium oxide matrix, and drying, wherein during the slurrying process, the zirconium oxide matrix is ​​introduced in two steps. The catalyst of the invention is used for catalytic thermal cracking of heavy oil, with high raw material conversion rate and good light olefin selectivity.

[0004] The prior art does not involve the treatment of waste liquid containing titanium tetrachloride generated during the preparation of titanium-based polypropylene catalysts. Moreover, the modified ZSM-5 molecular sieve and the corresponding catalytic cracking catalyst do not involve reducing the tendency to form coke and reducing the yield of heavy oil. It is necessary to provide a new technology for preparing catalytic cracking catalysts that has a simple and feasible preparation process and excellent performance. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a catalytic cracking catalyst and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides a catalytic cracking catalyst, which comprises a catalyst component A and a catalyst component B in a weight ratio of 98:2-20:80;

[0007] Taking the weight of the raw materials of catalyst component A as 100%, the raw materials of catalyst component A include: 15%-55% of modified ZSM-5 molecular sieve, 10%-55% of clay, 3%-20% of aluminum source, and 5%-20% of phosphorus from a second modifier, the weight of the modified ZSM-5 molecular sieve, clay, and aluminum source are calculated on a dry basis, and the weight of the phosphorus is calculated on an oxide basis;

[0008] The modified ZSM-5 molecular sieve is obtained by modifying the raw material ZSM-5 molecular sieve with a first modifier; the first modifier includes a titanium source and a phosphorus source, the titanium source is used to provide titanium in the modified ZSM-5 molecular sieve, and the phosphorus source is used to provide phosphorus in the modified ZSM-5 molecular sieve;

[0009] Taking the weight of the raw materials of catalyst component B as 100%, the raw materials of catalyst component B include: 15%-50% Y-type molecular sieve, 10%-55% clay, 5%-30% aluminum source, and 3%-20% binder; wherein the weight of the Y-type molecular sieve, clay, and aluminum source are calculated on a dry basis, and the weight of the binder is calculated on an oxide basis.

[0010] According to a specific embodiment of the present invention, the weight ratio of the catalyst component A to the catalyst component B can be 98:2-20:80, for example, 97:3-30:70. In some specific embodiments, the weight ratio of the catalyst component A to the catalyst component B can be 98:2, 97:3, 96:4, 95:5, 94:6, 93:7, 92:8, 91:9, 90:10, 85:15, 80:20, 75:25, 70:30 and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0011] In the modified ZSM-5 molecular sieve, the titanium source and the phosphorus source in the first modifier can jointly modify the ZSM-5 molecular sieve, synergistically improve the acid distribution and hydrothermal stability in the ZSM-5 molecular sieve, thereby promoting the conversion of heavy oil in the catalytic process involving the catalytic cracking catalyst and reducing the amount of coke produced.

[0012] In the above-mentioned modified ZSM-5 molecular sieve, based on the total weight of the modified ZSM-5 molecular sieve being 100%, the modified ZSM-5 molecular sieve includes 0.2%-25% of titanium from the first modifier and 0.2%-6% of phosphorus from the first modifier; wherein the weights of the titanium and phosphorus are respectively calculated as oxides.

[0013] In the modified ZSM-5 molecular sieve, the weight content of the titanium from the first modifier in the modified ZSM-5 molecular sieve is 0.2%-25%, and further can be 0.5%-15%. Specifically, the weight content of the titanium from the first modifier in the modified ZSM-5 molecular sieve can be 0.2%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0014] In the modified ZSM-5 molecular sieve, the weight content of phosphorus from the first modifier in the modified ZSM-5 molecular sieve is 0.2%-6%, and further can be 0.5%-6%. Specifically, the weight content of phosphorus from the first modifier in the modified ZSM-5 molecular sieve can be 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, etc., and a range with any two of the above specific values ​​as endpoints, calculated as phosphorus oxide.

[0015] In the modified ZSM-5 molecular sieve, the modified ZSM-5 molecular sieve may further include a modified metal element, and accordingly, the first modifier may further include a modified metal source for providing the modified metal element. The modified metal element may modify the ZSM-5 molecular sieve to improve the hydrothermal stability, acidity and catalytic reaction performance of the ZSM-5 molecular sieve.

[0016] In some specific embodiments, the weight proportion of the modified metal element from the first modifier in the modified ZSM-5 molecular sieve is 0-5%, such as greater than 0% and less than or equal to 5%, calculated as the oxide of the modified metal element; further, it can be 0.5%-5%, 0-3%, etc. Specifically, the weight proportion of the modified metal element from the first modifier in the modified ZSM-5 molecular sieve can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., and a range with any two of the above specific values ​​as endpoints, calculated as the oxide of the modified metal element.

[0017] In the above-mentioned catalytic cracking catalyst, the preparation method of the modified ZSM-5 molecular sieve includes: mixing the raw material ZSM-5 with a titanium source to form a mixed solution, performing a first calcination, or fully impregnating the raw material ZSM-5 molecular sieve with an impregnation solution containing a titanium source, drying, and performing a first calcination; mixing the product of the first calcination with a phosphorus source, performing a second calcination, and obtaining the modified ZSM-5 molecular sieve.

[0018] The preparation method of the modified ZSM-5 molecular sieve has no special restrictions on the mixing conditions of the titanium source and the raw material ZSM-5 molecular sieve, and the mixing conditions of the first calcined product and the phosphorus source, as long as the components are fully mixed. In some specific embodiments, the mixing temperature of the titanium source and the raw material ZSM-5 molecular sieve can be 4-150°C, and the mixing time can be 10min-2h. The mixing temperature of the first calcined product and the phosphorus source can be 4-150°C, and the mixing time can be 10min-2h.

[0019] In the preparation method of the modified ZSM-5 molecular sieve, the temperature of the first calcination is 450-650°C, and the time of the first calcination is 1-4h. Specifically, the temperature of the first calcination can be 450°C, 500°C, 550°C, 600°C, 650°C, and other specific values, and any two of the above specific values ​​are the range of endpoints. The time of the first calcination is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, and other specific values, and any two of the above specific values ​​are the range of endpoints.

[0020] In the preparation method of the modified ZSM-5 molecular sieve, the temperature of the second calcination is 450-650°C, and the time of the second calcination is 1-4h. Specifically, the temperature of the second calcination can be 450°C, 500°C, 550°C, 600°C, 650°C, and other specific values, and any two of the above specific values ​​are the range of endpoints. The time of the second calcination is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, and other specific values, and any two of the above specific values ​​are the range of endpoints.

[0021] In the above-mentioned preparation method of ZSM-5 molecular sieve, when the first modifier includes a modified metal source, the modified metal source is usually mixed with the titanium source and the raw material ZSM-5 molecular sieve to avoid precipitation between the phosphorus source and the metal.

[0022] In the above-mentioned preparation method of ZSM-5 molecular sieve, the silicon-aluminum ratio of the raw material ZSM-5 molecular sieve can be 15-450. In some specific embodiments, the raw material ZSM-5 molecular sieve can be a ZSM-5 molecular sieve with a higher silicon-aluminum ratio. Specifically, the silicon-aluminum ratio of the raw material ZSM-5 molecular sieve can be 20-450, 30-450, etc.

[0023] In the above-mentioned preparation method of ZSM-5 molecular sieve, the raw material ZSM-5 molecular sieve may include a micromesoporous ZSM-5 molecular sieve, that is, a molecular sieve containing micropores and mesopores; in some specific embodiments, the mesopore volume of the micromesoporous ZSM-5 molecular sieve may be not less than 0.10 mL / g, for example, it may be 0.10-0.70 mL / g, 0.10-30 mL / g, 0.30-0.70 mL / g, etc.

[0024] In the above-mentioned method for preparing ZSM-5 molecular sieve, the raw material ZSM-5 molecular sieve may be added in the form of slurry, and the slurry may be formed by dispersing the raw material ZSM-5 molecular sieve in water.

[0025] In the above-mentioned method for preparing the ZSM-5 molecular sieve, the pH value of the mixed solution and / or the impregnating solution can be controlled to be 0.5-8, for example, 0.5-3. The present invention is beneficial to control the distribution of titanium in the ZSM-5 molecular sieve by controlling the pH value range of the mixed solution and / or the impregnating solution. In some specific embodiments, the pH value of the mixed solution and / or the impregnating solution can be 0.5, 1, 1.5, 1.8, 2, 3, 4, 5, 6, 7, 8 and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0026] According to a specific embodiment of the present invention, the preparation method of the modified ZSM-5 molecular sieve may further include adjusting the pH value of the titanium source and the modified metal source of the first modifier to 0.5-8, for example 0.5-3, and then mixing the titanium source, the modified metal source and the raw material ZSM-5 molecular sieve. By pre-adjusting the pH value of the titanium source and the modified metal source, it is possible to avoid the molecular sieve dealumination caused by the excessive acidity of the system when the titanium source, the modified metal source and the ZSM-5 molecular sieve are mixed. In addition, by controlling the range of the pH value, the distribution of modifying elements such as titanium in the modified ZSM-5 molecular sieve can be regulated.

[0027] In some specific embodiments, the pH value of the mixed solution, the impregnation solution, the titanium source, and the modified metal source can be adjusted by a pH adjuster, and the pH adjuster includes an alkaline substance. The alkaline substance can include one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, magnesium oxide, magnesium hydroxide, and magnesium carbonate.

[0028] According to a specific embodiment of the present invention, the preparation method of the modified ZSM-5 molecular sieve may include adjusting the pH value of the titanium source of the first modifier and the modified metal source to 0.5-8, filtering, and then mixing the filter cake obtained by filtration with the raw material ZSM-5 molecular sieve.

[0029] In the preparation method of the modified ZSM-5 molecular sieve, the mixed solution and / or the impregnation solution further comprises a dispersant, which can promote the full dispersion of the metal elements and titanium in the modified metal source, and is beneficial to improving the hydrothermal stability of the modified ZSM-5 molecular sieve.

[0030] In some specific embodiments, the mass of the dispersant can be 0-20% of the weight of the raw material ZSM-5 molecular sieve, such as 0.2-20%, 0-10%, and can be further controlled to be 0.3%-6%. In some specific embodiments, the weight ratio of the dispersant to the raw material ZSM-5 molecular sieve can be 0.1%, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20% and other specific values ​​and a range in which any two of the above specific values ​​are endpoints.

[0031] In the above preparation method, the dispersant includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.

[0032] In the preparation process of the modified ZSM-5 molecular sieve, the dispersant can be added once or in batches. Specifically, when the dispersant is added once, the dispersant can be added to the mixed solution and / or the impregnation solution, that is, the dispersant is added together with the titanium source, the modified metal source, and the raw material ZSM-5 molecular sieve. This addition method helps to improve the dispersibility of the titanium element and the modified metal element; alternatively, the dispersant can also be added together with the phosphorus source, and this addition method can improve the dispersibility of the phosphorus element. When the dispersant is added in batches, part of the dispersant can be added to the mixed solution containing the titanium source, the modified metal, and the raw material ZSM-5 molecular sieve or the impregnation solution containing the titanium source and the modified metal source, and the remaining dispersant is added together with the phosphorus source to achieve the effect of improving the dispersibility of titanium, phosphorus, and the modified metal elements in the molecular sieve.

[0033] According to a specific embodiment of the present invention, the raw material of the catalyst component A includes a second modifier, the second modifier includes a phosphorus source, and 5%-20% of the phosphorus contained in the raw material of the catalyst component A comes from the second modifier.

[0034] In some specific embodiments, the phosphorus content in the raw material of the catalyst A component may be 6% to 19% by weight, calculated as phosphorus oxide, and the phosphorus comes from the second modifier.

[0035] In some specific embodiments, phosphorus is calculated as oxide, and the weight proportion of phosphorus in the raw material of catalyst component A can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% and other specific values, as well as ranges with any two of the above specific values ​​as endpoints.

[0036] According to a specific embodiment of the present invention, the second modifier may also include a titanium source, and the raw material of the catalyst A component contains 0-10%, such as 0.2%-10%, 0.5%-8%, of titanium in the form of oxide from the second modifier, based on the weight of the catalyst A component as 100%. In some specific embodiments, the titanium is calculated as oxide, and the weight content of the titanium from the second modifier in the raw material of the catalyst A component can be 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., as well as a range with any two of the above specific values ​​as endpoints.

[0037] According to a specific embodiment of the present invention, the titanium contained in the catalyst component A may exist in the form of ions inside and on the surface of the modified ZSM-5 molecular sieve, or may be used as a carrier in the catalyst in the form of oxides.

[0038] According to a specific embodiment of the present invention, the weight of the titanium source in the second modifier can be 0-9.9% of the weight of the raw material of the catalyst component A, for example, greater than 0 and less than 9.9%. In some specific embodiments, the weight proportion of the titanium source in the second modifier in the raw material of the catalyst component A can be 0.1%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.9% and other specific values ​​and ranges with any two of the above specific values ​​as endpoints.

[0039] According to a specific embodiment of the present invention, the second modifier may also include a modified metal source. Based on the weight of catalyst component A being 100%, the raw material of catalyst component A contains 0-5%, such as 0-3%, 0.2%-5%, of modified metal elements in terms of oxide from the second modifier.

[0040] In some specific embodiments, phosphorus is calculated as oxide, and its weight proportion in the raw material of catalyst component A can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% and other specific values, as well as ranges with any two of the above specific values ​​as endpoints.

[0041] In the above catalytic cracking catalyst, the catalyst component A may further include a binder.

[0042] In the above catalytic cracking catalyst, the weight of the binder calculated as an oxidant is 0-10% of the weight of the catalyst component A, and can further be 0-6%. In some specific embodiments, the binder is calculated as an oxide, and the weight proportion of the binder in the raw material of the catalyst component A is 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and other specific values, and a range with any two of the above specific values ​​as endpoints.

[0043] In the above catalytic cracking catalyst, the raw material of the catalyst component A is calculated as 100%, and the raw material of the catalyst component A includes 15%-55%, for example, 20%-50% of the modified ZSM-5 molecular sieve on a dry basis. In some specific embodiments, the modified ZSM-5 molecular sieve is calculated on a dry basis, and the weight proportion of the modified ZSM-5 molecular sieve in the raw material of the catalyst component A can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0044] In the above catalytic cracking catalyst, the raw material of the catalyst component A is 100% by weight, and the raw material of the catalyst component A includes 10%-55%, for example, 10%-50% clay on a dry basis. In some specific embodiments, the weight proportion of clay in the raw material of the catalyst component A on a dry basis can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, and other specific values, as well as ranges with any two of the above specific values ​​as endpoints.

[0045] In the above catalytic cracking catalyst, the raw material of the catalyst component A is calculated as 100% by weight, and the raw material of the catalyst component A includes 3%-20%, for example, 3%-15% of the aluminum source on a dry basis. In some specific embodiments, the aluminum source is calculated on a dry basis, and the weight proportion of the aluminum source in the raw material of the catalyst component A can be 3%, 5%, 10%, 15%, 20%, and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0046] In the above catalytic cracking catalyst, the clay and aluminum source in the catalyst component A can synergistically act with the phosphorus source in the first modifier to improve the adhesion between the components in the catalyst component A, thereby improving the anti-wear performance of the catalyst component A.

[0047] In the above-mentioned catalytic cracking catalyst, based on the total weight of catalyst component A as 100%, the raw materials of catalyst component A include 20%-50% of modified ZSM-5 molecular sieve calculated on a dry basis, 10%-50% of clay calculated on a dry basis, 3%-15% of pseudo-boehmite calculated on a dry basis, 6%-19% of phosphorus calculated on an oxide basis, 0-6% of a binder calculated on an oxide basis, 0.5%-8% of titanium calculated on an oxide basis and 0-3% of a modified metal compound calculated on an oxide basis.

[0048] In the above-mentioned catalytic cracking catalyst, the raw material of the catalyst component B also includes a third modifier, and the third modifier also includes a modified metal source for providing a modified metal element, and the raw material of the catalyst component B also includes 0-5%, for example, 0.5%-3%, of the modified metal element in terms of oxide from the third modifier. In some specific embodiments, the modified metal element is calculated as oxide, and the weight proportion of the modified metal element from the third modifier in the raw material of the catalyst component B can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc., and a range with any two of the above specific values ​​as endpoints.

[0049] In the above catalytic cracking catalyst, the raw material of the catalyst B component is 100% by weight, and the raw material of the catalyst B component also includes 0-10% of the ZSM-5 molecular sieve on a dry basis; preferably, the raw material of the catalyst B component is 100% by weight, and the raw material of the catalyst B component also includes 0-8% of the ZSM-5 molecular sieve on a dry basis. In some specific embodiments, the ZSM-5 molecular sieve in the raw material of the catalyst B component is 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and a range with any two of the above specific values ​​as endpoints.

[0050] The ZSM-5 molecular sieve includes a raw material ZSM-5 molecular sieve and / or a modified ZSM-5 molecular sieve. The preparation method and component composition of the modified ZSM-5 molecular sieve can refer to the preparation method and component composition of the modified ZSM-5 molecular sieve in the catalyst A component; the raw material ZSM-5 molecular sieve is an unmodified ZSM-5 molecular sieve.

[0051] In the above catalytic cracking catalyst, the raw material of the catalyst B component includes 15%-50%, for example, 20%-45%, of Y-type molecular sieve on a dry basis, based on 100% by weight of the raw material of the catalyst B component. In some specific embodiments, the Y molecular sieve is calculated on a dry basis, and the weight proportion of the Y molecular sieve in the raw material of the catalyst B component is 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., and a range with any two of the above specific values ​​as endpoints.

[0052] In the above catalytic cracking catalyst, the raw material of the catalyst component B includes 10%-55% clay on a dry basis, based on 100% by weight of the raw material of the catalyst component B. In some specific embodiments, the clay is calculated on a dry basis, and the weight proportion of the clay in the raw material of the catalyst component B is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, etc., and a range with any two of the above specific values ​​as endpoints.

[0053] In the above catalytic cracking catalyst, the raw material of the catalyst component B is 100% by weight, and the raw material of the catalyst component B includes 5-30%, for example, 5%-25% of the aluminum source on a dry basis. In some specific embodiments, the aluminum source is calculated on a dry basis, and the weight proportion of the aluminum source in the raw material of the catalyst component B is 5%, 10%, 15%, 20%, 25%, 30%, and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0054] In the above catalytic cracking catalyst, the raw material of the catalyst component B includes 3%-20%, for example, 3%-15%, of a binder on a dry basis, based on 100% by weight of the raw material of the catalyst component B. In some specific embodiments, the binder is calculated as an oxide, and the weight proportion of the binder in the raw material of the catalyst component B is 3%, 5%, 10%, 15%, and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0055] In the above-mentioned catalytic cracking catalyst, based on the total weight of the raw materials of catalyst component B as 100%, the raw materials of catalyst component B include 0-8% of ZSM-5 molecular sieve on a dry basis, 20%-45% of Y-type molecular sieve on a dry basis, 10%-55% of clay on a dry basis, 5%-25% of aluminum source on a dry basis, 3%-15% of binder on an oxide basis, 2%-15% of inorganic oxide support material on an oxide basis and 0.5%-3% of modified metal on an oxide basis.

[0056] In the above catalytic cracking catalyst, the catalyst component B may further include an inorganic oxide carrier, and the raw material of the catalyst component B may include 0-30%, for example, 2%-15%, of inorganic oxide carrier material in terms of oxide, based on the weight of the raw material of the catalyst component B being 100%. In some specific embodiments, the inorganic oxide carrier material is calculated as oxide, and the weight proportion of the inorganic oxide carrier material in the raw material of the catalyst component B may be 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0057] In some specific embodiments, the inorganic oxide carrier includes one or a combination of two or more of white carbon black, an alumina material containing a Brønsted acid center, and a silicon-alumina material containing a Brønsted acid center. The alumina material containing a Brønsted acid center and the silicon-alumina material containing a Brønsted acid center have high pore volume, large specific surface area, double pore distribution, high thermal stability and high acid content, and contain a Brønsted acid center.

[0058] In the preparation process of the above-mentioned catalytic cracking catalyst, in the first modifier, the second modifier, and the third modifier, the modified metal element may include one or a combination of two or more of the elements iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium, and yttrium. In some specific embodiments, the modified metal source includes a metal salt and / or a metal oxide. The metal salt may include one or a combination of two or more of chlorides, nitrates, carbonates, sulfates, oxalates, and acetates.

[0059] In the above-mentioned modified ZSM-5 molecular sieve, the phosphorus source in the first modifier and the second modifier includes one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphate, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate; preferably, the phosphorus source includes one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, magnesium phosphate, aluminum phosphate, phosphorous acid, ammonium phosphite, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.

[0060] In the first modifier and the second modifier, the titanium source refers to a substance containing titanium element, and specifically may include titanium tetrachloride. Further, the titanium source includes a combination of titanium tetrachloride and hexane; in some specific embodiments, the weight ratio of titanium tetrachloride to hexane may be (4-34):1, for example, 4:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 34:1 and other specific values, and a range with any two of the above specific values ​​as endpoints.

[0061] According to a specific embodiment of the present invention, the titanium source in the first modifier and / or the second modifier comprises a waste liquid containing titanium tetrachloride, and the waste liquid containing titanium tetrachloride contains titanium tetrachloride and may further contain hydrocarbons such as hexane.

[0062] The titanium tetrachloride-containing waste liquid can be specifically the titanium tetrachloride-containing waste liquid obtained in the production process of titanium-based polyolefin (such as polypropylene) catalyst. Taking the total weight of the titanium tetrachloride-containing waste liquid as 100%, the titanium tetrachloride-containing waste liquid includes 80%-95% titanium tetrachloride, 2%-5% alkoxy titanium complex, and the remainder is hydrocarbon; wherein the hydrocarbon is liquid at room temperature, including hexane and esters, and most of it is hexane.

[0063] In the above-mentioned waste liquid containing titanium tetrachloride, titanium tetrachloride can be used to modify ZSM-5 molecular sieves; hexane can promote the uniform distribution of titanium in ZSM-5 molecular sieves, increase the pore volume of modified ZSM-5 molecular sieves, and thus improve the diffusion effect of molecules in modified ZSM-5 molecular sieves and improve the catalytic reaction selectivity of modified ZSM-5 molecular sieves. In addition, hydrocarbons such as hexane present in the titanium tetrachloride solution can form micropores, mesopores, etc. after calcination, which is beneficial to improve the pore structure of the catalyst and enhance the catalytic activity.

[0064] In some specific embodiments, the titanium tetrachloride-containing waste liquid can be generated during the preparation of titanium-based polypropylene catalysts. The above preparation method can solve the problem of waste liquid treatment, save treatment costs, and avoid environmental pollution by using a large amount of titanium tetrachloride-containing waste liquid generated during the preparation of titanium-based polypropylene catalysts as raw materials.

[0065] The titanium sources used in the first modifier and the second modifier may be the same or different.

[0066] In the above-mentioned catalytic cracking catalyst, in the catalyst component A and / or the catalyst component B, the clay includes one or a combination of two or more of kaolin, montmorillonite, diatomite, halloysite (also known as halloysite), sepiolite, and bentonite. Specifically, the clay may include one of kaolin, diatomite, halloysite, or sepiolite. The clays used in the catalyst component A and the catalyst component B may be the same or different.

[0067] In the above-mentioned catalytic cracking catalyst, in the catalyst component A and / or the catalyst component B, the aluminum source may include one or a combination of two or more of pseudo-boehmite, amorphous alumina, boehmite, aluminum nitrate, and aluminum chloride. In some specific embodiments, the aluminum source may be pseudo-boehmite. The aluminum sources used in the catalyst component A and the catalyst component B may be the same or different.

[0068] In the above catalytic cracking catalyst, in the catalyst component A and / or the catalyst component B, the binder includes one or a combination of two or more of aluminum sol, silica sol, silica-alumina sol, and phosphoalumina sol. The binders used in the catalyst component A and the catalyst component B can be the same or different.

[0069] In the above-mentioned catalytic cracking catalyst, in the catalyst B component, the Y-type molecular sieve includes one or a combination of two or more of HY molecular sieve, NH4Y molecular sieve, hydrothermal ultra-stable Y-type molecular sieve, silicon tetrachloride vapor phase ultra-stable Y-type molecular sieve, rare earth-containing Y-type molecular sieve, and phosphorus-modified ultra-stable Y-type molecular sieve. Specifically, the rare earth-containing Y-type molecular sieve includes a rare earth-modified ultra-stable Y-type molecular sieve and / or a phosphorus-and-rare earth-modified ultra-stable Y-type molecular sieve.

[0070] The present invention also provides a method for preparing the above-mentioned catalytic cracking catalyst, comprising:

[0071] Preparation of catalyst component A: mixing the modified ZSM-5 molecular sieve, clay, aluminum source and the second modifier and beating the mixture to form a first slurry; spray drying and calcining the first slurry to obtain the catalyst component A;

[0072] Preparation of catalyst component B: Y-type molecular sieve, clay, aluminum source, and binder are mixed and slurried to form a second slurry; the second slurry is spray-dried and calcined to obtain the catalyst component B; the third modifier includes a modified metal source;

[0073] The catalyst A component and the catalyst B component are mixed to obtain the catalytic cracking catalyst.

[0074] In the preparation process of the catalytic cracking catalyst, the second modifier includes at least a phosphorus source, and may further include a modified metal source and a titanium source.

[0075] In the preparation process of the catalytic cracking catalyst, the second slurry may further include a third modifier, and the third modifier includes at least a modified metal source.

[0076] In the preparation process of the above-mentioned catalytic cracking catalyst, by introducing a second modifier into the catalyst component A and a third modifier into the catalyst component B, the content of the modifying element (titanium, modifying metal element, etc.) in the catalytic cracking catalyst can be further increased.

[0077] According to a specific embodiment of the present invention, the pH value of the titanium source in the second modifier can be 0.5-8. In the preparation process of catalyst A component, the pH value of the titanium source can be adjusted to 0.5-8, and then the titanium source is mixed with the modified ZSM-5 molecular sieve. When the second modifier includes a higher acidity of the modified metal source (such as an iron source, etc.), the pH value of the modified metal source can also be adjusted to 0.5-8, and then the modified metal source is mixed with the modified ZSM-5 molecular sieve.

[0078] In some specific embodiments, the pH value of the titanium source and the modified metal source of the second modifier can be adjusted by using an alkaline substance. The alkaline substance can include one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, magnesium oxide, magnesium hydroxide, and magnesium carbonate.

[0079] According to a specific embodiment of the present invention, the preparation method can adjust the pH value of the titanium source and the modified metal source of the second modifier to 0.5-8, then filter, and add the obtained filter cake as the second modifier to the first slurry.

[0080] According to a specific embodiment of the present invention, by adjusting the pH value of the second modifier in advance, it is possible to avoid the modified ZSM-5 molecular sieve from being dealuminated due to excessive acidity of the system when mixed with the second modifier. In addition, by controlling the pH value range, the distribution of modifying elements such as titanium in the ZSM-5 molecular sieve can be controlled.

[0081] In the above-mentioned method for preparing the catalytic cracking catalyst, the modified ZSM-5 molecular sieve can be added in the form of slurry, and the volume median particle size (D(v, 0.5)) of the modified ZSM-5 molecular sieve slurry can be less than or equal to 4 μm (that is, the particle size of particles accounting for 50% by volume can be less than or equal to 4 μm). In some specific embodiments, the modified ZSM-5 molecular sieve can be pre-grinded.

[0082] In the above method for preparing the catalytic cracking catalyst, the volume median particle size D (v, 0.5) of the first slurry and / or the second slurry is less than or equal to 4 μm. The slurry may be sand-milled before spray drying.

[0083] In the above-mentioned method for preparing the catalytic cracking catalyst, the first slurry and / or the second slurry may further include a pore structure improver, which can improve the pore structure, specific surface area and other structural properties of the catalyst. The pore structure improver is added to the first slurry and the second slurry, and the weight of the pore structure improver is 0.1%-10%, preferably 0.3%-5% of the total weight of the catalytic cracking catalyst.

[0084] In the above method for preparing the catalytic cracking catalyst, the weight of the pore structure improver contained in the first slurry is 0.3%-6% of the weight of the raw material of the catalyst A component.

[0085] In the above-mentioned method for preparing the catalytic cracking catalyst, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.

[0086] According to a specific embodiment of the present invention, the process of preparing the catalyst component A may further include acidifying at least one of the modified ZSM-5 molecular sieve and clay and the aluminum source; the process of preparing the catalyst component B may further include acidifying at least one of the binder, clay, and at least part of the modified metal source in the second modifier and the aluminum source. Acidification during the preparation of the catalyst components A and B can acidify and disperse the aluminum source such as pseudo-boehmite, so that the aluminum source such as pseudo-boehmite has a certain binder effect, thereby improving the anti-wear performance of the catalytic cracking catalyst.

[0087] According to a specific embodiment of the present invention, the acid used in the acidification treatment may include an inorganic acid, which may include one or a combination of two or more of hydrochloric acid, sulfuric acid, and nitric acid.

[0088] According to a specific embodiment of the present invention, the temperature of the acidification treatment may be 40-90° C., and the time of the acidification treatment may be 0.5-3 h.

[0089] The present invention also provides the use of the above-mentioned catalytic cracking catalyst in a catalytic cracking process. The above-mentioned catalytic cracking catalyst is used in the catalytic cracking process, which can promote the conversion of heavy oil, reduce the yield of heavy oil, reduce the tendency of coking, and at the same time, the yield of light olefins and aromatics is high. For relatively heavy crude oil, the Y molecular sieve in the above-mentioned catalytic cracking catalyst can first crack the heavy oil macromolecules, and then allow the cracked products to enter the ZSM-5 molecular sieve for further conversion into chemical products such as light olefins and aromatics.

[0090] In some specific embodiments, the reaction temperature of the catalytic cracking process may be 530-650° C., and the catalyst-oil ratio may be 8-20.

[0091] The beneficial effects of the present invention include:

[0092] 1. The component A and component B in the catalytic cracking catalyst provided by the present invention are used in a mixed manner, and have the following synergistic effects: the catalyst B can convert heavy oil macromolecules into relatively small molecules, wherein straight-chain hydrocarbons or straight-chain hydrocarbons containing methyl groups can enter the catalyst A to continue the reaction, and crack into smaller molecules, especially light olefins (ethylene, propylene, butene). However, such a reaction effect cannot be achieved by using the catalyst component A or the catalyst component B alone. Moreover, compared with the catalyst containing both the Y-type molecular sieve and the ZSM-5 molecular sieve, the catalyst system formed by mixing the catalyst component A and the catalyst component B of the present invention has a higher yield of light olefins and better selectivity.

[0093] 2. The present invention uses a catalytic cracking catalyst with a modified ZSM-5 molecular sieve as an active component for use in a catalytic cracking process, which can promote the conversion of heavy oil in the catalytic cracking process, reduce the heavy oil yield, and reduce the tendency to produce coke while producing more low-carbon olefins such as ethylene / propylene, and has excellent reaction selectivity and performance. Furthermore, the raw material for preparing the catalytic cracking catalyst provided by the present invention can include waste liquid containing titanium tetrachloride generated in the preparation process of the titanium-based polypropylene catalyst, which not only solves the problem of treating the waste liquid and avoids its environmental pollution, but also reduces the high treatment cost of the waste liquid. BRIEF DESCRIPTION OF THE DRAWINGS

[0094] Figure 1 It is the BJH pore distribution curve of carrier material APM-7 and industrial pseudo-boehmite. DETAILED DESCRIPTION

[0095] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0096] In the following examples and comparative examples, the content of elements such as titanium, phosphorus, and modified metal in the modified ZSM-5 molecular sieve is determined by X-ray fluorescence analysis. The crystallinity of ZSM-5 is relative crystallinity, which is measured by XRD method. The specific surface area retention rate is the ratio of the specific surface area of ​​the modified molecular sieve before aging to the specific surface area after aging multiplied by 100%. The pore volume of the molecular sieve is measured by Micromeritics ASAP3000 automatic physical adsorption instrument, N2 isothermal adsorption-desorption.

[0097] In the present invention, the dry basis refers to the state of the material after being calcined at 800° C. for 1 hour.

[0098] The origin and specifications of the raw materials used in the embodiments of the present invention are as follows:

[0099] (1) Waste liquid containing titanium tetrachloride generated during the preparation of titanium-based polypropylene catalyst (hereinafter referred to as waste liquid containing titanium tetrachloride): based on the total weight of the waste liquid as 100%, the waste liquid includes 90% titanium (in terms of TiCl4), 2-5% alkoxytitanium complex, and the remainder is hydrocarbons in liquid form at room temperature; the hydrocarbons are mainly hexane and the remainder is esters. The waste liquid was provided by the Lanzhou Chemical Research Center of the PetroChina Petrochemical Research Institute.

[0100] Kaolin (burn-off 29wt%), halloysite (burn-off 16.6wt%), pseudo-boehmite (burn-off 36wt%), aluminum sol (containing 21.6wt% alumina), silica sol (silicon oxide concentration 30wt%), ordinary ZSM-5 molecular sieve (silicon-aluminum ratio 31, mesoporous volume 0.04mL / g), high-silicon ZSM-5 molecular sieve (silicon-aluminum ratio 384), USY molecular sieve (Na2O content 1.2wt%, no rare earth, reduced by 4wt%), GUSY-1 molecular sieve (silicon tetrachloride vapor phase ultra-stable molecular sieve, Na2O content 1.3wt%, RE2O3 content 2.7wt%, relative crystallinity 55%, unit cell constant Reduce by 4wt%), REHY molecular sieve (Na2O content 1.5wt%, RE2O3 content 8.2wt%, reduce by 5wt%), rare earth chloride solution (RE2O3 content 289.3g / L): all are industrial products, collected from the catalyst plant of Lanzhou Petrochemical Company.

[0101] (2) Micro-mesoporous ZSM-5 molecular sieve: Si-Al ratio 30, mesopore volume 0.29 mL / g, purchased from Dalian;

[0102] (3) Diatomaceous earth (ignition loss 2.6 wt%): industrial product, purchased from Inner Mongolia Autonomous Region;

[0103] (4) Titanium tetrachloride, magnesium oxide, magnesium chloride, phosphoric acid (concentration 85%), ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lanthanum oxide, yttrium nitrate, ferric nitrate (Fe(NO3)3·9H2O), zirconium oxide, zirconium sulfate, 1,3,5-trimethylbenzene, polyethylene glycol, carboxymethyl cellulose: all are chemical reagents; n-hexane: analytical grade reagent.

[0104] (5) Hydrochloric acid: concentration 36%, chemical reagent; nitric acid: concentration 65-68%, chemical reagent; ammonia water: concentration 18%, chemical reagent.

[0105] (6) The carrier material APM-7 used in the following examples and comparative examples is an active silicon-aluminum material produced by the catalyst plant of PetroChina Lanzhou Petrochemical Company. The carrier material APM-7 has a Br acid center. The carrier material is prepared from cheap silicon and aluminum sources, and the pH value of the system is adjusted by hydrochloric acid and ammonia water. The multi-level porous silicon-aluminum material with rich Br acid characteristics is prepared by gelling, heating and aging, etc. The preparation method of the Br acid-rich multi-level porous material APM-7 is described in "Application of Br acid-rich multi-level porous material in catalytic cracking catalyst" (Fine Petrochemicals, 2019, 36 (3): 24-27.), and the full text of the above document is introduced here as part of the specification.

[0106] Figure 1 It is the BJH pore distribution curve of the carrier material APM-7 and the comparative material (industrial pseudo-boehmite, also known as industrial alumina). Figure 1 It can be seen that APM-7 has two pore distributions: medium pores and large pores, while industrial pseudo-boehmite material has only a single pore distribution between 2-4nm, and the pore diameter is 3.4nm.

[0107] Table 1 shows the infrared acid characterization data of the carrier material APM-7 and industrial pseudo-boehmite (comparative material).

[0108] Table 1

[0109]

[0110] As can be seen from Table 1, the total amount of L acid and B acid of APM-7 is 91.50 and 197.36 μmol / g respectively, and the B / L acid ratio is as high as 2.2. The comparative material only contains L acid centers, and the total amount of L acid is 213.61 μmol / g, which is lower than that of APM-7.

[0111] In the following examples and comparative examples, the furnace temperature of the spray drying was 450°C and the spray exhaust temperature was 200°C.

[0112] Example 1

[0113] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof includes:

[0114] 1. Preparation of modified ZSM-5 molecular sieve:

[0115] (1) 1.402 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, stirred evenly, and then 139 g of waste liquid containing titanium tetrachloride was added, stirred for 0.5 h to form a slurry containing the molecular sieve, dried at 120 ° C, and calcined at 500 ° C for 1 h; wherein the pH value of the slurry containing the molecular sieve was 1.01;

[0116] (2) The molecular sieve calcined in step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120° C., and calcined at 500° C. for 1 h to obtain a titanium-phosphorus-modified micro-mesoporous ZSM-5 molecular sieve Z-1.

[0117] Calculated based on the amount of raw materials added, the titanium-phosphorus modified ZSM-5 molecular sieve Z-1 contains 3.5% titanium (calculated as oxide), 3.0% phosphorus (calculated as oxide), and the remainder is ZSM-5 molecular sieve.

[0118] 2. Preparation of catalyst component A:

[0119] 1.08 kg of kaolin (dry basis), 0.36 kg of pseudo-boehmite (dry basis) and 4.05 L of deionized water were added to a beating tank for beating, stirred for 1 hour, and then 48 mL of hydrochloric acid was added, stirred for 0.5 hour, and then acidified at 50° C. for 2 hours to obtain a first intermediate system;

[0120] Then, 1.08 kg of titanium-phosphorus modified microporous ZSM-5 molecular sieve Z-1 (dry basis), 0.799 kg of phosphoric acid and 30 g of carboxymethyl cellulose were added to the first intermediate system and mixed and slurried for 1 hour. The first slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried and calcined at 550°C for 2 hours to obtain catalytic cracking catalyst component A CAT-A1.

[0121] The raw material composition of catalytic cracking catalyst component A CAT-A1 is: 36wt% (dry basis) of titanium-phosphorus modified microporous ZSM-5 molecular sieve Z-1, 36wt% (dry basis) of kaolin, 12wt% (dry basis) of pseudo-boehmite, and 16wt% of phosphorus pentoxide from the phosphoric acid added in step 2.

[0122] 3. Preparation of catalyst component B:

[0123] 1.413 kg of kaolin (dry basis), 0.972 kg of aluminum sol and 1.52 kg of deionized water were added to a slurrying tank for slurrying. Then, 0.24 kg of pseudo-boehmite (dry basis) and 15 g of lanthanum oxide were added and stirred for 0.5 h. Then, 36 mL of hydrochloric acid was added and stirred for 2 h. The mixture was acidified at 70 ° C for 1.5 h to obtain a second intermediate system.

[0124] 1.05 kg of USY molecular sieve (dry basis), 183 g of yttrium nitrate, 91.5 g of magnesium chloride and 1.58 kg of deionized water were mixed and slurried for 1.5 h, then added to the second intermediate system of the first slurrying tank, and then 30 g of carboxymethyl cellulose was added and slurried for 2 h. The obtained second slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst B component microspheres.

[0125] The catalyst B component microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the catalytic cracking catalyst B component CAT-B1.

[0126] The raw material composition of the catalytic cracking catalyst B component CAT-B1 is: 47.1wt% (dry basis) of kaolin, 8wt% (dry basis) of pseudo-boehmite, 7wt% of aluminum oxide from aluminum sol, 35wt% (dry basis) of USY molecular sieve, 1.8wt% of yttrium oxide from yttrium nitrate, 0.6wt% of magnesium oxide from magnesium chloride, 0.5wt% of lanthanum oxide, and 38% of catalyst gel solid content. The catalyst gel solid content is the solid content in the raw material slurry, that is, the ratio of the solid mass (dry basis) obtained after spray drying to the mass of the raw material slurry before spray drying.

[0127] The catalyst A component CAT-A1 and the catalyst B component CAT-B1 were mixed at a weight ratio of 98:2 to obtain the catalytic cracking catalyst CAT-1 of this example.

[0128] Example 2

[0129] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof includes:

[0130] 1. Preparation of modified ZSM-5 molecular sieve:

[0131] (1) 1.388 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) and 15 g of polyethylene glycol were added to 3.5 L of deionized water, and stirred evenly. Then, 20 g of waste liquid containing titanium tetrachloride and 103 g of zirconium sulfate were added, and stirred for 1.5 h to form a slurry containing the molecular sieve, which was dried at 100 ° C. and calcined at 550 ° C. for 1.5 h; wherein the pH value of the slurry containing the molecular sieve was 1.52;

[0132] (2) Mix the molecular sieve calcined in step (1) with 15g polyethylene glycol and 3.5L deionized water, add 97g phosphoric acid, stir evenly, dry at 100°C, and calcine at 550°C for 1.5h to obtain a titanium-zirconium-phosphorus-modified microporous ZSM-5 molecular sieve Z-2. Calculated according to the amount of raw materials added, the titanium-zirconium-phosphorus-modified ZSM-5 molecular sieve Z-2 contains 0.5% titanium (in terms of oxide), 3.0% zirconium (in terms of oxide), 4.0% phosphorus (in terms of oxide), and the remainder is ZSM-5 molecular sieve.

[0133] 2. Preparation of catalyst component A:

[0134] 1.14 kg of kaolin (dry basis), 0.12 kg of pseudo-boehmite (dry basis) and 4.18 L of deionized water were added to a beating tank for beating, stirred for 0.5 h, and then 12.1 mL of hydrochloric acid was added, stirred for 15 min, and then acidified at 50° C. for 1 h to obtain a first intermediate system;

[0135] Then add 0.972kg aluminum sol, 1.14kg titanium-zirconium-phosphorus modified microporous ZSM-5 molecular sieve Z-2 (dry basis), 30g lanthanum oxide, 0.585kg phosphoric acid and 15g polyethylene glycol to the first intermediate system, mix and slurry for 0.5h, and then subject the obtained first slurry to sand milling so that the average particle size D (v, 0.5) of the slurry is less than 4μm. Then, spray dry and calcine at 500°C for 1h to obtain catalytic cracking catalyst component A CAT-A2.

[0136] The raw material composition of catalytic cracking catalyst component A CAT-A2 is: 38wt% (dry basis) of titanium-zirconium-phosphorus modified microporous ZSM-5 molecular sieve Z-2, 38wt% (dry basis) of kaolin, 4wt% (dry basis) of pseudo-boehmite, 7wt% of alumina from aluminum sol, 1wt% of lanthanum oxide, and 12wt% of phosphorus pentoxide from the phosphoric acid added in step 2.

[0137] 3. Preparation of catalyst component B:

[0138] 1.08 kg of kaolin (dry basis), 0.972 kg of aluminum sol and 1.7 kg of deionized water were added to a slurrying tank for slurrying, and then 0.54 kg of pseudo-boehmite (dry basis) and 155 mL of rare earth chloride solution were added, stirred for 1.5 hours, and then 91 mL of hydrochloric acid was added. After stirring for 0.5 hours, acidification was performed at 50°C for 1 hour to obtain a second intermediate system.

[0139] 0.9 kg of GUSY-1 molecular sieve (dry basis), 60 g of the titanium-phosphorus-zirconium modified micro-mesoporous ZSM-5 molecular sieve Z-2 (dry basis) in the above-mentioned component A, 45 g of yttrium chloride (calculated as yttrium oxide) and 1.6 kg of deionized water were mixed and slurried for 0.5 h, and then added to the second intermediate system of the first slurrying tank, and then 120 g (dry basis) of the carrier material APM-7 and 15 g of polyethylene glycol were added, and slurried for 1 h. The obtained second slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst component B microspheres.

[0140] The catalyst B component microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the catalytic cracking catalyst B component CAT-B2.

[0141] The raw material composition of catalytic cracking catalyst component B CAT-B2 is: 36wt% (dry basis) of kaolin, 18wt% (dry basis) of pseudo-boehmite, 7wt% of alumina from aluminum sol, 30wt% (dry basis) of GUSY-1 molecular sieve, 2wt% (dry basis) of titanium-phosphorus-zirconium modified microporous ZSM-5 molecular sieve Z-2, 1.5wt% of yttrium oxide from yttrium chloride, 1.5wt% of rare earth oxide from rare earth chloride solution, 4wt% of inorganic oxide carrier material APM-7 (dry basis), and the solid content of the catalyst gel is 36%.

[0142] The catalyst A component CAT-A2 and the catalyst B component CAT-B2 were mixed at a weight ratio of 95:5 to obtain the catalytic cracking catalyst CAT-2 of this example.

[0143] Example 3

[0144] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof includes:

[0145] 1. Preparation of modified ZSM-5 molecular sieve:

[0146] (1) Under stirring, 792 g of waste liquid containing titanium tetrachloride, 113.6 g of ferric nitrate, and 110 g of carboxymethyl cellulose were added to 3.6 L of deionized water, stirred for 10 min, and the pH value was adjusted to 6.51 with ammonia water. Then, 1.102 kg of ordinary ZSM-5 molecular sieve (dry basis) was added and stirred for 1 h to form a molecular sieve-containing slurry, which was dried at 100° C. and calcined at 520° C. for 1 h; wherein the pH value of the molecular sieve slurry was 5.66;

[0147] (2) The molecular sieve calcined in step (1), 110 g of carboxymethyl cellulose and 3.6 L of deionized water were mixed, 139 g of diammonium hydrogen phosphate was added, stirred evenly, dried at 100° C., and calcined at 520° C. for 1 h to obtain titanium iron phosphorus modified ZSM-5 molecular sieve Z-3.

[0148] Calculated based on the amount of raw materials added, the titanium-iron-phosphorus modified ZSM-5 molecular sieve contains 20.0% titanium (in terms of oxide), 1.5% iron (in terms of oxide), 5.0% phosphorus (in terms of oxide), and the remainder is ZSM-5 molecular sieve.

[0149] 2. Preparation of catalyst component A:

[0150] 1.5 kg ZSM-5 molecular sieve Z-3 (dry basis) was added into 4 L deionized water, stirred, and sand-milled to make the average particle size D (v, 0.5) of the molecular sieve Z-3 slurry less than 4 μm.

[0151] The above-mentioned molecular sieve Z-3 slurry with an average particle size D (v, 0.5) less than 4 μm, 0.93 kg of halloysite (dry basis), 0.18 kg of pseudo-boehmite (dry basis) and 0.7 L of deionized water were added to a pulping tank for pulping and stirred for 2 hours, and then 22.7 mL of hydrochloric acid was added. After stirring for 25 minutes, it was acidified at 70°C for 1 hour and cooled to 35°C to obtain a first intermediate system; 694 g of aluminum sol, 0.390 kg of phosphoric acid and 150 g of carboxymethyl cellulose were added to the first intermediate system, and after mixing and pulping for 0.5 hours, the obtained first slurry was homogenized, spray dried and calcined at 600°C for 3 hours to obtain catalytic cracking catalyst A component CAT-A3.

[0152] The raw material composition of catalytic cracking catalyst component A CAT-A3 is: 50wt% (dry basis) of titanium iron phosphorus modified ZSM-5 molecular sieve Z-3, 31wt% (dry basis) of halloysite, 6wt% (dry basis) of pseudo-boehmite, 5wt% of alumina from aluminum sol, and 8wt% of phosphorus pentoxide from the phosphoric acid added in step 2.

[0153] 3. Preparation of catalyst component B:

[0154] 1.236 kg of kaolin (dry basis), 1.11 kg of aluminum sol, 15 g of cerium oxide and 1.74 kg of deionized water were added to a slurrying tank for slurrying. Then 0.24 kg of pseudo-boehmite (dry basis) was added and stirred for 1 hour. Then 20 mL of nitric acid was added and stirred for 1 hour. The mixture was acidified at 50°C for 1.2 hours to obtain a second intermediate system.

[0155] 0.72 kg of GUSY-1 molecular sieve (dry basis), 0.24 kg of REHY molecular sieve (dry basis), 60 g of titanium-phosphorus-zirconium modified micro-mesoporous ZSM-5 molecular sieve Z-2 in component A of Example 2 (dry basis), 0.18 kg of unmodified high-silicon ZSM-5 molecular sieve (dry basis), 54 g of yttrium oxide, 15 g of magnesium oxide and 1.98 kg of deionized water were mixed and slurried for 0.5 h, then added to the second intermediate system of the first slurrying tank, and 150 g of carboxymethyl cellulose was added and slurried for 1.8 h. The obtained second slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst component B microspheres.

[0156] The catalyst B component microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the catalytic cracking catalyst B component CAT-B3.

[0157] The raw material composition of catalytic cracking catalyst component B CAT-B3 is: 41.2wt% (dry basis) of kaolin, 8wt% (dry basis) of pseudo-boehmite, 8wt% (dry basis) of alumina from aluminum sol, 24wt% (dry basis) of GUSY-1 molecular sieve, 8wt% (dry basis) of REHY molecular sieve, 2wt% (dry basis) of micro-mesoporous ZSM-5 molecular sieve Z-2, 6wt% (dry basis) of high-silicon ZSM-5 molecular sieve, 1.8wt% of yttrium oxide, 0.5wt% of cerium oxide, 0.5wt% of magnesium oxide, and the solid content of the catalyst gel is 36%.

[0158] The catalyst A component CAT-A3 and the catalyst B component CAT-B3 were mixed at a weight ratio of 70:30 to obtain the catalytic cracking catalyst CAT-3 of this example.

[0159] Example 4

[0160] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof includes:

[0161] 1. Preparation of catalyst component A:

[0162] 0.96 kg of titanium-phosphorus-modified micro-mesoporous ZSM-5 molecular sieve Z-1 (dry basis) of component A of Example 1 was added into 2.2 L of deionized water, stirred, and sand-milled to make the average particle size D (v, 0.5) of the molecular sieve Z-1 slurry less than 4 μm.

[0163] 30 g of magnesium oxide was added to 1.8 L of deionized water, stirred, 475 g of waste liquid containing titanium tetrachloride was added, the pH value was adjusted to 7 with ammonia water, filtered, and a filter cake A containing titanium and magnesium was obtained.

[0164] 1.065 kg of kaolin (dry basis), 0.24 kg of pseudo-boehmite (dry basis) and 1.5 L of deionized water were added to a pulping tank and pulped, stirred for 40 minutes, and then 28.2 mL of hydrochloric acid was added. After stirring for 15 minutes, the mixture was acidified at 45°C for 1.5 hours to obtain a first intermediate system; 600 g of silica sol, the above-mentioned molecular sieve Z-1 slurry with an average particle size D (v, 0.5) less than 4 μm, filter cake A, 0.487 kg of phosphoric acid, 45 g of zirconium oxide, and 9 g of 1,3,5-trimethylbenzene were added to the first intermediate system. After mixing and pulping for 1 hour, the obtained first slurry was homogenized, spray dried, and calcined at 570°C for 1.5 hours to obtain catalytic cracking catalyst A component CAT-A4.

[0165] The raw material composition of catalytic cracking catalyst component A CAT-A4 is: 32wt% (dry basis) of modified micro-mesoporous ZSM-5 molecular sieve Z-1, 35.5wt% (dry basis) of kaolin, 8wt% (dry basis) of pseudo-boehmite, 6wt% of silicon oxide from silica sol, 1.5wt% of zirconium oxide, 6wt% (oxide) of titanium from filter cake A, 1wt% (oxide) of magnesium from filter cake A, and 10wt% of phosphorus pentoxide from phosphoric acid.

[0166] 2. Preparation of catalyst component B:

[0167] 0.45 kg of kaolin (dry basis), 0.3 kg of halloysite (dry basis), 0.833 kg of aluminum sol and 1.76 kg of deionized water were added to a slurrying tank for slurrying, and then 0.75 kg of pseudo-boehmite (dry basis) was added and stirred for 1 hour. Then 101 mL of hydrochloric acid was added and stirred for 0.5 hour, and then acidified at 55°C for 2 hours to obtain a second intermediate system.

[0168] 1.26 kg of GUSY-1 molecular sieve (dry basis), 60 g of yttrium oxide and 2.1 kg of deionized water were mixed and slurried for 0.5 h, then added to the second intermediate system of the first slurrying tank, and then 9 g of 1,3,5-trimethylbenzene was added and slurried for 1.5 h. The obtained second slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried to obtain catalyst B component microspheres.

[0169] The catalyst B component microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the catalytic cracking catalyst B component CAT-B4.

[0170] The raw material composition of the catalytic cracking catalyst B component CAT-B4 is: 15wt% (dry basis) of kaolin, 10wt% (dry basis) of halloysite, 25wt% (dry basis) of pseudo-boehmite, 6wt% of alumina from aluminum sol, 42wt% (dry basis) of GUSY-1 molecular sieve, 2wt% of yttrium oxide, and 36% of catalyst gel solid content. The catalyst gel solid content is the solid content in the slurry, that is, the ratio of the mass of the solid obtained after spray drying to the mass of the slurry before spray drying.

[0171] Catalyst A component CAT-A4 and catalyst B component CAT-B4 were mixed at a weight ratio of 30:70 to obtain the catalytic cracking catalyst CAT-4 of this example.

[0172] Example 5

[0173] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof includes:

[0174] 1. Preparation of modified ZSM-5 molecular sieve:

[0175] (1) Weigh 170.6 g of Fe(NO3)3·9H2O and 107 g of waste liquid containing titanium tetrachloride, dissolve them in an appropriate volume of distilled water to prepare a mixed impregnation solution of ferric nitrate / titanium tetrachloride, wherein the pH value of the mixed impregnation solution of ferric nitrate / titanium tetrachloride is 0.56; slowly pour the mixed impregnation solution into 1.381 kg of ordinary ZSM-5 molecular sieve (dry basis), stirring continuously to achieve equal volume impregnation; after standing for 12 hours, put it into a 120°C oven to dry for 6 hours; calcine it in a muffle furnace at 540°C for 4 hours to obtain the modified molecular sieve Fe-Ti / ZSM-5;

[0176] (2) The Fe-Ti / ZSM-5 molecular sieve modified in step (1) was mixed with 3.6 L of deionized water, 73 g of ammonium dihydrogen phosphate was added, stirred evenly, dried at 120° C., and calcined at 520° C. for 1 h to obtain a titanium iron phosphorus modified ZSM-5 molecular sieve Z-4.

[0177] Calculated based on the amount of raw materials added, the titanium-iron-phosphorus modified ZSM-5 molecular sieve contains 2.7% titanium (calculated as oxide), 2.25% iron (calculated as oxide), 3.0% phosphorus (calculated as oxide), and the remainder is ZSM-5 molecular sieve.

[0178] 2. Preparation of catalyst component A:

[0179] 0.78 kg of kaolin (dry basis), 0.18 kg of diatomaceous earth (dry basis), 0.3 kg of pseudo-boehmite (dry basis) and 4.18 L of deionized water were added to a pulping tank for pulping, stirred for 0.5 h, and then 25 mL of nitric acid was added. After stirring for 45 min, the mixture was acidified at 55 ° C for 2 h to obtain a first intermediate system; 1.26 kg of ZSM-5 molecular sieve Z-4 ​​(dry basis), 0.799 kg of phosphoric acid and 30 g of polyethylene glycol were added to the first intermediate system, and after mixing and pulping for 1 h, the obtained first slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried, and calcined at 500 ° C for 2 h to obtain catalytic cracking catalyst A component CAT-A5.

[0180] The raw material composition of catalytic cracking catalyst component A CAT-A5 is: 42wt% (dry basis) of titanium iron phosphorus modified ZSM-5 molecular sieve Z-4, 26wt% (dry basis) of kaolin, 6wt% (dry basis) of diatomaceous earth, 10wt% (dry basis) of pseudo-boehmite, and 16wt% of phosphorus pentoxide from the phosphoric acid added in step 2.

[0181] Catalyst A component CAT-A5 and catalyst B component CAT-B4 prepared in Example 4 were mixed at a weight ratio of 90:10 to obtain the catalytic cracking catalyst CAT-5 of this example.

[0182] Example 6

[0183] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof includes:

[0184] 1. Preparation of modified ZSM-5 molecular sieve:

[0185] (1) 1.402 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, and stirred evenly. Then 125 g of titanium tetrachloride was added, and stirred for 0.5 h to form a slurry containing the molecular sieve (as a mixed liquid), which was dried at 120° C. and calcined at 500° C. for 1 h. The pH value of the slurry containing the molecular sieve was 1.03.

[0186] (2) The calcined product of step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120 °C, and calcined at 500 °C for 1 h to obtain a titanium-phosphorus-modified micro-mesoporous ZSM-5 molecular sieve, denoted as Z-5.

[0187] Calculated according to the amount of raw materials added, the composition of the titanium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve is: 3.5% titanium (calculated as oxide), 3.0% phosphorus (calculated as oxide), and the balance is ZSM-5 molecular sieve.

[0188] 2. Preparation of catalyst component A: The preparation method is similar to that of catalyst component A in Example 1, except that the modified ZSM-5 molecular sieve used in this example is the titanium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve in step 1 of this example.

[0189] 3. Preparation of catalyst component B: The preparation method is the same as that of catalyst component B in Example 1.

[0190] Catalyst A component CAT-A6 and catalyst B component CAT-B1 were mixed at a weight ratio of 98:2 to obtain the catalytic cracking catalyst CAT-6 of this example.

[0191] Example 7

[0192] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof includes:

[0193] 1. Preparation of modified ZSM-5 molecular sieve:

[0194] (1) Under stirring, 712 g of titanium tetrachloride, 113.6 g of ferric nitrate, 21 g of n-hexane, and 110 g of carboxymethyl cellulose were added to 3.6 L of deionized water, stirred for 10 min, the pH value was adjusted to 6.51 with aqueous ammonia, and then 1.102 kg of ordinary ZSM-5 molecular sieve (dry basis) was added, stirred for 1 h to form a slurry containing molecular sieve, dried at 100 ° C, and calcined at 520 ° C for 1 h; wherein the pH value of the slurry containing molecular sieve is 5.70;

[0195] (2) The calcined product of step (1), 110 g of carboxymethyl cellulose and 3.6 L of deionized water were mixed, and 139 g of diammonium hydrogen phosphate was added. The mixture was stirred evenly, dried at 100° C., and calcined at 520° C. for 1 h to obtain a titanium iron phosphorus modified ZSM-5 molecular sieve, which was recorded as Z-6.

[0196] Calculated based on the amount of raw materials added, the titanium-iron-phosphorus modified ZSM-5 molecular sieve Z-6 contains 20.0% titanium (calculated as oxide), 1.5% iron (calculated as oxide), and 5.0% phosphorus (calculated as oxide).

[0197] 2. Preparation of catalyst component A: The preparation method is similar to that of catalyst component A in Example 3, except that the modified ZSM-5 molecular sieve used in this example is the titanium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve in step 1 of this example.

[0198] 3. Preparation of catalyst component B: The preparation method is the same as that of catalyst component B in Example 3.

[0199] Catalyst A component CAT-A7 and catalyst B component CAT-B3 were mixed at a weight ratio of 70:30 to obtain the catalytic cracking catalyst CAT-7 of this example.

[0200] Comparative Example 1

[0201] This comparative example provides a catalytic cracking catalyst, the preparation method of which comprises:

[0202] 1. Preparation of modified ZSM-5 molecular sieve:

[0203] (1) adding 1.455 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) into 4 L of deionized water, stirring for 0.5 h to form a slurry containing the molecular sieve, drying at 120° C., and calcining at 500° C. for 1 h; wherein the pH value of the slurry containing the molecular sieve is 2.51;

[0204] (2) The molecular sieve calcined in step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120° C., and calcined at 500° C. for 1 h to obtain a phosphorus-modified micro-mesoporous ZSM-5 molecular sieve DZ-1.

[0205] Calculated based on the amount of raw materials added, the phosphorus-modified ZSM-5 molecular sieve contains 3.0% phosphorus (in terms of oxide), and the remainder is ZSM-5 molecular sieve.

[0206] 2. Preparation of catalyst component A:

[0207] 1.08 kg of kaolin (dry basis), 0.36 kg of pseudo-boehmite (dry basis) and 4.05 L of deionized water were added to a pulping tank and pulped, stirred for 1 hour, and then 48 mL of hydrochloric acid was added. After stirring for 0.5 hour, the mixture was acidified at 50°C for 2 hours. Then 1.08 kg of micro-mesoporous ZSM-5 molecular sieve DZ-1 (dry basis) and 0.799 kg of phosphoric acid were added, mixed and pulped for 1 hour, homogenized, spray dried, and calcined at 550°C for 2 hours to obtain comparative catalytic cracking catalyst A component DCAT-A1.

[0208] The raw material composition of the comparative catalytic cracking catalyst component A DCAT-A1 is: 36wt% (dry basis) of modified micro-mesoporous ZSM-5 molecular sieve DZ-1, 36wt% (dry basis) of kaolin, 12wt% (dry basis) of pseudo-boehmite, and 16wt% of phosphorus pentoxide from the phosphoric acid added in step 2.

[0209] 3. Preparation of catalyst component B:

[0210] 1.413 kg of kaolin (dry basis), 0.972 kg of aluminum sol and 1.52 kg of deionized water were added to a pulping tank for pulping, and then 0.24 kg of pseudo-boehmite (dry basis) and 15 g of lanthanum oxide were added, stirred for 0.5 h, and then 36 mL of hydrochloric acid was added. After stirring for 2 h, acidification was performed at 70 ° C for 1.5 h.

[0211] 1.05 kg of USY molecular sieve (dry basis), 183 g of yttrium nitrate, 91.5 g of magnesium chloride and 1.58 kg of deionized water were mixed and slurried for 1.5 hours, then added to the first slurrying tank, slurried for 2 hours, homogenized, and spray-dried to obtain catalyst B component microspheres.

[0212] The catalyst B component microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the catalytic cracking catalyst B component DCAT-B1.

[0213] The raw material composition of catalytic cracking catalyst component B DCAT-B1 is: 47.1wt% (dry basis) of kaolin, 8wt% (dry basis) of pseudo-boehmite, 7wt% of aluminum oxide from aluminum sol, 35wt% (dry basis) of USY molecular sieve, 1.8wt% of yttrium oxide from yttrium nitrate, 0.6wt% of magnesium oxide from magnesium chloride, 0.5wt% of lanthanum oxide, and the solid content of the catalyst gel is 38%.

[0214] The catalyst A component DCAT-A1 and the catalyst B component DCAT-B1 were mixed at a weight ratio of 98:2 to obtain the catalytic cracking catalyst DCAT-1 of this comparative example.

[0215] Comparative Example 2

[0216] This comparative example provides a catalytic cracking catalyst, the preparation method of which comprises:

[0217] 1. Preparation of modified ZSM-5 molecular sieve:

[0218] (1) 1.455 kg of ordinary ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, stirred for 0.5 h to form a slurry containing molecular sieve, dried at 120 ° C, and calcined at 500 ° C for 1 h;

[0219] (2) The molecular sieve calcined in step (1) was mixed with 4 L of deionized water, 73 g of phosphoric acid was added, stirred evenly, dried at 120° C., and calcined at 500° C. for 1 h to obtain phosphorus-modified ZSM-5 molecular sieve DZ-2.

[0220] Calculated based on the amount of raw materials added, the phosphorus-modified ZSM-5 molecular sieve contains 3.0% phosphorus (in terms of oxide), and the remainder is ZSM-5 molecular sieve.

[0221] 2. Preparation of catalyst component A:

[0222] 1.08 kg of kaolin (dry basis), 0.36 kg of pseudo-boehmite (dry basis) and 4.05 L of deionized water were added to a pulping tank and pulped, stirred for 1 hour, and then 48 mL of hydrochloric acid was added, stirred for 0.5 hour and acidified at 50°C for 2 hours; then 1.08 kg of ZSM-5 molecular sieve DZ-2 (dry basis), 0.799 kg of phosphoric acid and 30 g of carboxymethyl cellulose were added, mixed and pulped for 1 hour, homogenized, spray dried and calcined at 550°C for 2 hours to obtain comparative catalytic cracking catalyst A component DCAT-A2.

[0223] The raw material composition of the comparative catalytic cracking catalyst component A DCAT-A2 is: 36wt% (dry basis) of modified ZSM-5 molecular sieve DZ-2, 36wt% (dry basis) of kaolin, 12wt% (dry basis) of pseudo-boehmite, and 16wt% of phosphorus pentoxide from the phosphoric acid added in step 2.

[0224] This comparative example provides a catalytic cracking catalyst, wherein the catalyst B component is the catalyst B component CAT-B1 prepared in Example 1. Catalyst A component DCAT-A2 and catalyst B component CAT-B1 are mixed at a weight ratio of 98:2 to obtain the catalytic cracking catalyst DCAT-2 of this comparative example.

[0225] Comparative Example 3

[0226] This comparative example provides a catalytic cracking catalyst, the preparation method of which comprises:

[0227] 1. Preparation of modified ZSM-5 molecular sieve:

[0228] (1) Weigh 170.6 g of Fe(NO3)3·9H2O and 96 g of titanium tetrachloride, dissolve them in an appropriate volume of distilled water to prepare a mixed impregnation solution of ferric nitrate / titanium tetrachloride, slowly pour the mixed impregnation solution into 1.426 kg of ordinary ZSM-5 molecular sieve (dry basis), stir continuously to achieve equal volume impregnation; let it stand for 12 hours, then put it in a 120°C oven to dry for 6 hours; calcine it in a muffle furnace at 540°C for 4 hours to obtain the modified molecular sieve DZ-3;

[0229] Calculated based on the amount of raw materials added, the titanium-iron modified ZSM-5 molecular sieve contains 2.7% titanium (calculated as oxide), 2.25% iron (calculated as oxide), and the remainder is ZSM-5 molecular sieve.

[0230] 2. Preparation of catalyst component A:

[0231] 0.78 kg of kaolin (dry basis), 0.18 kg of diatomaceous earth (dry basis), 0.3 kg of pseudo-boehmite (dry basis) and 4.18 L of deionized water were added to a pulping tank and pulped, stirred for 0.5 h, and then 25 mL of nitric acid was added, stirred for 45 min, and then acidified at 55 ° C for 2 h; then 1.26 kg of ZSM-5 molecular sieve DZ-3 (dry basis), 0.799 kg of phosphoric acid, and 30 g of polyethylene glycol were added, mixed and pulped for 1 h, homogenized, spray dried, and calcined at 500 ° C for 2 h to obtain the comparative catalytic cracking catalyst A component DCAT-A3.

[0232] The raw material composition of the comparative catalytic cracking catalyst component A DCAT-A3 is: 42wt% (dry basis) of modified ZSM-5 molecular sieve DZ-3, 26wt% (dry basis) of kaolin, 6wt% (dry basis) of diatomaceous earth, 10wt% (dry basis) of pseudo-boehmite, and 16wt% of phosphorus pentoxide from the phosphoric acid added in step 2.

[0233] The catalyst A component DCAT-A3 and the catalyst B component (CAT-B4 prepared in Example 4) were mixed at a weight ratio of 90:10 to obtain the catalytic cracking catalyst DCAT-3 of this comparative example.

[0234] Comparative Example 4

[0235] This comparative example provides a catalytic cracking catalyst, and its preparation method is as follows:

[0236] 0.504 kg of kaolin (dry basis), 0.3 kg of halloysite (dry basis), 0.833 kg of aluminum sol and 1.83 kg of deionized water were added to a slurrying tank for slurrying. Then 0.75 kg of pseudo-boehmite (dry basis) was added and stirred for 1 hour. Then 101 mL of hydrochloric acid was added and stirred for 0.5 hour, and then acidified at 55°C for 2 hours.

[0237] 0.126 kg of GUSY-1 molecular sieve (dry basis), 1.134 kg of ZSM-5 molecular sieve DZ-3 prepared in Comparative Example 3 (dry basis), 6 g of yttrium oxide and 1.96 kg of deionized water were mixed and slurried for 0.5 h, then added to the first step slurrying tank, slurried for 1.5 h, homogenized, and spray-dried to obtain catalyst microspheres.

[0238] The catalyst microspheres obtained by spray drying are calcined, washed to reduce sodium, and dried to obtain the catalytic cracking catalyst DCAT-4 of this comparative example.

[0239] The raw material composition of the catalytic cracking catalyst DCAT-4 is: 16.8wt% (dry basis) of kaolin, 10wt% (dry basis) of halloysite, 25wt% (dry basis) of pseudo-boehmite, 6wt% of alumina from aluminum sol, 4.2wt% (dry basis) of GUSY-1 molecular sieve, 37.8wt% (dry basis) of ZSM-5 molecular sieve DZ-3, 0.2wt% of yttrium oxide, and the solid content of the catalyst gel is 36%.

[0240] Comparative Example 5

[0241] This comparative example provides a catalytic cracking catalyst, the preparation method of which comprises:

[0242] 1. Preparation of modified ZSM-5 molecular sieve:

[0243] (1) 1.402 kg of micro-mesoporous ZSM-5 molecular sieve (dry basis) was added to 4 L of deionized water, stirred evenly, and then 73 g of phosphoric acid was added, stirred evenly, dried at 120 ° C, and calcined at 500 ° C for 1 h;

[0244] (2) The calcined product of step (1) was mixed with 4 L of deionized water, 139 g of waste liquid containing titanium tetrachloride was added, and the mixture was stirred for 0.5 h to form a slurry containing molecular sieves. The mixture was stirred evenly, dried at 120 ° C, and calcined at 500 ° C for 1 h to obtain a phosphorus-titanium modified micro-mesoporous ZSM-5 molecular sieve, which was recorded as DZ-4.

[0245] The phosphorus-titanium modified micro-mesoporous ZSM-5 molecular sieve comprises: 3.5% titanium (calculated as oxide), 3.0% phosphorus (calculated as oxide), and the balance ZSM-5 molecular sieve.

[0246] 2. Preparation of catalyst component A: The preparation method is similar to that of catalyst component A in Example 1, except that the modified ZSM-5 molecular sieve used in this example is the titanium-phosphorus modified micro-mesoporous ZSM-5 molecular sieve in step 1 of this example.

[0247] 3. Preparation of catalyst component B: The preparation method is the same as that of catalyst component B in Example 1.

[0248] The catalyst A component and the catalyst B component were mixed at a weight ratio of 98:2 to obtain the catalytic cracking catalyst DCAT-5 of this comparative example.

[0249] The median particle size of the catalyst component A and the catalyst component B obtained in the above examples and comparative examples is 65-78 μm.

[0250] Test Example 1

[0251] (1) This test example provides the test results of the hydrothermal stability of the modified ZSM-5 molecular sieves prepared in the above examples and comparative examples.

[0252] The modified ZSM-5 molecular sieves prepared in Examples 1 to 3, 5 to 7 and the modified ZSM-5 molecular sieves prepared in Comparative Examples 1-3 and 5 were used as samples to be tested, and the specific surface areas of the samples to be tested were measured; then, each sample to be tested was aged for 17 hours at 800°C and 100% water vapor, and the specific surface areas of the samples to be tested after aging were measured, and the specific surface area retention rate was calculated. The results are listed in Table 2.

[0253] Table 2 Specific surface area retention test results of ZSM-5 molecular sieves in various embodiments and comparative examples

[0254]

[0255]

[0256] The results in Table 2 show that after aging at 800°C and 100% water vapor for 17 hours, the specific surface area retention rate of the ZSM-5 molecular sieve prepared by the preparation method of the present invention is higher than that of the comparative ZSM-5 molecular sieves DZ-1, DZ-2 and DZ-3 prepared in the comparative example.

[0257] The difference between Example 1 and Comparative Example 1 is only whether a titanium source is added. The specific surface area retention rate of the titanium-phosphorus modified ZSM-5 molecular sieve of Example 1 is 11.7% higher than that of the phosphorus-modified ZSM-5 molecular sieve of Comparative Example 1.

[0258] The modifying elements used in Example 5 and Comparative Example 3 are different. By comparison, it can be seen that the specific surface area retention rate of the titanium iron phosphorus modified ZSM-5 molecular sieve in Example 5 is 10.4% higher than the specific surface area retention rate of the titanium iron modified ZSM-5 molecular sieve in Comparative Example 3.

[0259] The difference between Comparative Example 5 and each embodiment (especially Example 6) is that the modification order of the phosphorus source and the titanium source is different. As can be seen from Table 2, compared with first modifying the ZSM-5 molecular sieve with phosphorus and then modifying the ZSM-5 molecular sieve with titanium, the reaction order of first modifying the ZSM-5 molecular sieve with titanium and then modifying the ZSM-5 molecular sieve with phosphorus adopted in the present invention can significantly improve the specific surface area retention rate of the molecular sieve, and the increase can reach more than 8 percentage points. The above results show that the present invention can effectively improve the hydrothermal stability of the ZSM-5 molecular sieve by controlling the reaction order.

[0260] The types of titanium sources used in Example 1 and Example 6 are different. It can be seen from Table 2 that pure titanium tetrachloride and waste liquid containing titanium tetrachloride as titanium sources to modify the molecular sieve can improve the specific surface area retention rate of the molecular sieve to a certain extent; among them, compared with pure titanium tetrachloride, waste liquid containing titanium tetrachloride as a titanium source has a more obvious effect of improving hydrothermal stability.

[0261] The above results indicate that the preparation method of the present invention can significantly improve the hydrothermal stability of the titanium-phosphorus-modified ZSM-5 molecular sieve obtained by combining titanium and phosphorus as modifying elements and controlling the reaction order; on this basis, the performance of the ZSM-5 molecular sieve can be further improved by using iron, zirconium, zinc, magnesium, calcium, zirconium, lanthanum, cerium, and yttrium as the second metal for modification.

[0262] (2) This test example also provides the analysis results of the elemental composition of the modified ZSM-5 molecular sieves of the above embodiments and comparative examples. The content of each element in the samples of the above embodiments and comparative examples was tested by X-ray fluorescence analysis. The weight content of titanium, phosphorus, iron, and zirconium elements was calculated as oxides, and the weight content of chlorine element was calculated as Cl element. The test results are summarized in Table 3.

[0263] Table 3 Analysis results of element contents of modified ZSM-5 molecular sieves of various embodiments and comparative examples

[0264]

[0265] The main difference between Comparative Example 5 and each embodiment (especially Example 1) is that in Comparative Example 5, the ZSM-5 molecular sieve is first modified with phosphorus and then with titanium, while in the embodiment, the ZSM-5 molecular sieve is first modified with titanium and then with phosphorus. The results show that the Cl content in the modified ZSM-5 molecular sieves of each embodiment is close to 0, while the Cl content in the modified ZSM-5 molecular sieve of Comparative Example 5 is more than 7%, indicating that the modified ZSM-5 molecular sieve prepared by the embodiment of the present invention contains fewer impurities, and further indicating that the reaction sequence of the present invention can effectively reduce the impurity content in the modified ZSM-5 molecular sieve and improve the quality of the molecular sieve. In the catalytic cracking reaction process, if the chlorine content on the molecular sieve and the catalyst is too high, it is easy to cause corrosion and salt formation of the catalytic cracking device, which is not conducive to the long-term stable operation of the device.

[0266] The appearance color of the modified ZSM-5 molecular sieve (first titanium modification, then phosphorus modification) of each embodiment is white, while the appearance color of the modified ZSM-5 molecular sieve (first phosphorus modification, then titanium modification) of comparative example 5 is gray. This result shows that the template agent in the modified ZSM-5 molecular sieve of comparative example 5 is not easy to remove, and the template agent will block the molecular sieve pores, which has an adverse effect on the catalytic process; and the template agent in the modified ZSM-5 molecular sieve prepared by the present invention is easily removed by the roasting process, so as to avoid the situation that the template agent blocks the molecular sieve pores, which is conducive to improving the catalytic reaction selectivity of the molecular sieve. The measurement result of pore volume also shows that the pore volume of the modified ZSM-5 molecular sieve prepared by comparative example 5 is 0.25mL / g, and the pore volume of the modified ZSM-5 molecular sieve prepared by embodiment 1 is 0.31mL / g, indicating that the modified ZSM-5 molecular sieve prepared by the present invention has a relatively smooth pore structure.

[0267] The crystallinity of the ZSM-5 molecular sieves of the modified ZSM-5 molecular sieves of Example 1, Example 2, Example 6, Comparative Example 1 and Comparative Example 5 is analyzed, and the crystallinity results of each molecular sieve are as follows: the crystallinity of the molecular sieve of Example 1 is 65%, the crystallinity of the molecular sieve of Example 2 is 66%, the crystallinity of the molecular sieve of Example 6 is 65%, the crystallinity of the molecular sieve of Comparative Example 1 is 60%, and the crystallinity of the molecular sieve of Comparative Example 5 is 63%. The main difference between Comparative Example 1 and Example 1 and Example 2 is that Comparative Example 1 only uses phosphorus-modified ZSM-5 molecular sieves and does not use titanium modification. The molecular sieve is subjected to high-temperature calcination treatment during the modification process, which will cause the dealumination and structural destruction of the molecular sieve, so that the crystallinity of the molecular sieve measured by XRD is reduced, so the level of the crystallinity of the molecular sieve in the modified product can reflect the stability of the molecular sieve. Compared with the modified ZSM-5 molecular sieve prepared in Comparative Example 1, the crystallinity of the ZSM-5 molecular sieve in the modified ZSM-5 molecular sieves of Example 1, Example 2, and Example 6 is increased by more than 5 percentage points, indicating that the titanium-phosphorus synergistic modification makes the modified ZSM-5 molecular sieve prepared by the present invention better than the modified ZSM-5 molecular sieve of Comparative Example 1. Compared with the modified ZSM-5 molecular sieve of Comparative Example 5, the crystallinity of the ZSM-5 molecular sieve in the modified ZSM-5 molecular sieve of Example 1 is increased by 2 percentage points, while the crystallinity of the ZSM-5 molecular sieve in the modified ZSM-5 molecular sieve of Comparative Example 5 is relatively low, at 63%. This result also shows that the modified ZSM-5 molecular sieve prepared by the present invention is better than the modified ZSM-5 molecular sieve of Comparative Example 5. The above results show that the stability of the ZSM-5 molecular sieve can be effectively improved by synergistic modification of the ZSM-5 molecular sieve with titanium and phosphorus (further modification of modified metals such as zirconium can also be performed) and controlling the modification order.

[0268] Test Example 2

[0269] This test example is used to evaluate the performance of the catalytic cracking catalysts of Examples 1-4.

[0270] The catalytic cracking catalysts CAT-1, CAT-2, CAT-3, CAT-4, etc. prepared in Examples 1-4 and Examples 6-7, as well as the comparative catalytic cracking catalysts DCAT-1, DCAT-2, and DCAT-5 prepared in Comparative Examples 1, 2, and 5 were subjected to aging treatment at 800°C and 100% water vapor for 17 h, respectively, and then the catalytic cracking reaction performance was evaluated on a heavy oil micro-reactor evaluation device (ACE) using wax oil from Lanzhou Petrochemical Company as raw oil.

[0271] The reaction selectivity evaluation results of the catalytic cracking catalysts of Examples 1-4, Examples 6-7, Comparative Examples 1-2, and Comparative Example 5 are shown in Table 4.

[0272] In Table 4, total liquid yield = liquefied gas yield + gasoline yield + diesel yield; coke factor = (100-conversion rate) × coke yield / conversion rate.

[0273] Table 4

[0274]

[0275] Referring to Table 4, compared with the comparative catalytic cracking catalyst DCAT-2, the reaction conversion rate of the catalyst CAT-1 prepared in Example 1 increased by 0.71 percentage points, the total liquid yield (liquefied gas + gasoline + diesel) increased by 1.46 percentage points, the coke yield decreased by 1.09 percentage points, the coke factor decreased, and the yield of light olefins (ethylene + propylene + butene) increased by 3.02 percentage points, showing the characteristics of excellent heavy oil conversion, reduced coke production and high production of light olefins.

[0276] The above results show that compared with the comparative catalytic cracking catalysts DCAT-1, DCAT-2, and DCAT-5 of Comparative Examples 1, 2, and 5, the reaction conversion rate of the catalytic cracking catalysts CAT-1, CAT-2, CAT-3, and CAT-4 of the present invention is improved, the heavy oil yield is reduced, the coke factor is reduced, and the yield of light olefins (ethylene + propylene + butene) is increased. It shows that when the catalytic cracking catalyst prepared by the waste liquid containing titanium tetrachloride provided by the present invention is used, the efficient conversion of heavy oil is promoted, the tendency to produce coke is reduced, and light olefins are produced more at the same time, and the selectivity of the catalytic cracking reaction is improved.

[0277] The results in Table 4 also show that the catalysts prepared by using the combination of pure titanium tetrachloride, titanium tetrachloride and n-hexane in Example 6 and Example 7 also show the characteristics of reduced heavy oil, reduced coke factor and high yield of light olefins compared with the catalysts DCAT-1, DCAT-2 and DCAT-5 prepared in the comparative examples, indicating that the catalysts prepared by using the combination of pure titanium tetrachloride, titanium tetrachloride and n-hexane can improve the catalytic reaction selectivity of the catalyst.

[0278] Test Example 3

[0279] This test example is used to evaluate the performance of the catalytic cracking catalyst of Example 5.

[0280] The catalytic cracking catalyst CAT-5 prepared in Example 5 and the comparative catalytic cracking catalysts DCAT-3 and DCAT-4 prepared in Comparative Examples 3 and 4 were subjected to aging treatment at 800°C and 100% water vapor for 17 hours, respectively. Then, the catalytic cracking reaction performance was evaluated on a heavy oil micro-reactor evaluation device (ACE) using Lanzhou Petrochemical Company wax oil as raw oil.

[0281] The evaluation results of the catalytic cracking catalyst reaction selectivity of Example 5 and Comparative Examples 3-4 are shown in Table 5. In Table 5, total liquid yield = liquefied gas yield + gasoline yield + diesel yield; coke factor = (100-conversion rate) × coke yield / conversion rate.

[0282] Table 5

[0283]

[0284] Referring to Table 5, compared with the comparative catalyst DCAT-4, the reaction conversion rate of the catalytic cracking CAT-5 prepared in Example 5 increased by 1.12 percentage points, the coke yield decreased by 1.01 percentage points, the coke factor decreased, and the yield of light olefins (ethylene + propylene + butene) increased by 7.35 percentage points, showing the characteristics of excellent heavy oil conversion, reduced coke generation and high production of light olefins.

[0285] The results in Table 5 show that compared with the catalysts DCAT-3 and DCAT-4 of Comparative Examples 3 and 4, the reaction conversion rate of the catalytic cracking CAT-5 of the present invention is improved, the heavy oil yield is reduced, the coke factor is reduced, and the yield of light olefins (ethylene + propylene + butene) is increased. This shows that compared with the titanium-containing catalysts in the prior art, the use of the catalyst provided by the present invention can promote the efficient conversion of heavy oil, reduce the heavy oil yield, reduce the tendency to produce coke, produce more light olefins, and improve the selectivity of the catalytic cracking reaction.

[0286] The above test results indicate that the catalyst system formed by blending catalyst component A and component B of the present invention is used in the catalytic cracking process, which can promote the conversion of heavy oil in the catalytic cracking process, reduce the heavy oil yield, and reduce the tendency to form coke while producing more low-carbon olefins such as ethylene / propylene, and has excellent reaction selectivity and performance.

Claims

1. A catalytic cracking catalyst, comprising a catalyst component A and a catalyst component B in a weight ratio of 98:2-20:80; Taking the weight of the raw materials of catalyst component A as 100%, the raw materials of catalyst component A include: 15%-55% of modified ZSM-5 molecular sieve, 10%-55% of clay, 3%-20% of aluminum source, and 5%-20% of phosphorus from a second modifier, the weight of the modified ZSM-5 molecular sieve, clay, and aluminum source are calculated on a dry basis, and the weight of the phosphorus is calculated on an oxide basis; The modified ZSM-5 molecular sieve is obtained by modifying the raw material ZSM-5 molecular sieve with a first modifier; the first modifier includes a titanium source and a phosphorus source; Taking the weight of the raw materials of catalyst component B as 100%, the raw materials of catalyst component B include: 15%-50% Y-type molecular sieve, 10%-55% clay, 5%-30% aluminum source, and 3%-20% binder; wherein the weight of the Y-type molecular sieve, clay, and aluminum source are calculated on a dry basis, and the weight of the binder is calculated on an oxide basis.

2. The catalytic cracking catalyst according to claim 1, wherein The weight ratio of the catalyst A component to the catalyst B component is 97:3-30:

70.

3. The catalytic cracking catalyst according to claim 1, wherein Taking the total weight of the modified ZSM-5 molecular sieve as 100%, the modified ZSM-5 molecular sieve includes 0.2%-25% titanium from the first modifier and 0.2%-6% phosphorus from the first modifier; wherein the weights of the titanium and phosphorus are respectively calculated as oxides.

4. The catalytic cracking catalyst according to claim 1, wherein The modified ZSM-5 molecular sieve further includes a modified metal element, and the first modifier further includes a modified metal source; Preferably, the weight of the modified metal element from the first modifier, calculated as oxide, is 0-5% of the weight of the modified ZSM-5 molecular sieve.

5. The catalytic cracking catalyst according to claim 1 or 2, wherein: The preparation method of the modified ZSM-5 molecular sieve comprises: mixing the raw material ZSM-5 with the titanium source of the first modifier to form a mixed solution, performing a first calcination, or fully impregnating the raw material ZSM-5 molecular sieve with an impregnation solution containing the titanium source, drying, and performing a first calcination; mixing the product of the first calcination with the phosphorus source of the first modifier, performing a second calcination, and obtaining the modified ZSM-5 molecular sieve; Preferably, the temperature of the first calcination is 450-650°C, and the time of the first calcination is 1-4h; Preferably, the temperature of the second calcination is 450-650° C., and the time of the second calcination is 1-4 hours.

6. The catalytic cracking catalyst according to claim 5, wherein: The pH value of the mixed solution and / or the impregnation solution is 0.5-8; Preferably, the pH value of the mixed solution and / or the impregnating solution is 0.5-3.

7. The catalytic cracking catalyst according to claim 1, wherein The second modifier includes a phosphorus source; Preferably, the second modifier further comprises a titanium source, and based on 100% by weight of the catalyst A component, the raw material of the catalyst A component comprises 0-10% of titanium in the form of oxide from the second modifier.

8. The catalytic cracking catalyst according to claim 7, wherein: The second modifier also includes a source of modified metal. Based on 100% by weight of the catalyst A component, the raw material of the catalyst A component contains 0-5% of the modified metal element in terms of oxide from the second modifier.

9. The catalytic cracking catalyst according to claim 1, wherein: The raw materials of the catalyst A component also include a binder; Preferably, the weight of the binder calculated as the oxidant is 0-10% of the weight of the catalyst A component.

10. The catalytic cracking catalyst according to any one of claims 1 to 9, wherein: Taking the weight of the raw material of the catalyst component A as 100%, the raw material of the catalyst component A comprises 20% to 50% of the modified ZSM-5 molecular sieve on a dry basis; and / or, based on 100% by weight of the raw materials of the catalyst component A, the raw materials of the catalyst component A include 10% to 50% clay on a dry basis; and / or, based on 100% by weight of the raw material of the catalyst component A, the raw material of the catalyst component A comprises 3% to 15% on a dry basis of an aluminum source; And / or, based on 100% by weight of the raw material of the catalyst A component, the raw material of the catalyst A component comprises 6% to 19% of phosphorus in terms of oxide from the second modifier.

11. The catalytic cracking catalyst according to claim 5, wherein: Taking the weight of the raw material of catalyst component B as 100%, the raw material of catalyst component B also includes 0-10% ZSM-5 molecular sieve on a dry basis; the ZSM-5 molecular sieve includes the raw material ZSM-5 molecular sieve and / or modified ZSM-5 molecular sieve.

12. The catalytic cracking catalyst according to claim 1, wherein The raw material of the catalyst B component further comprises a third modifier, the third modifier further comprises a modifying metal source, and the raw material of the catalyst B component further comprises 0-5% of a modifying metal element calculated as oxide from the third modifier.

13. The catalytic cracking catalyst according to any one of claims 4, 8 or 12, wherein: The modified metal element includes one or a combination of two or more of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium.

14. The catalytic cracking catalyst according to claim 1 or 7, wherein: The titanium source includes titanium tetrachloride; Preferably, the titanium source comprises titanium tetrachloride and hexane in a weight ratio of (4-34):1; More preferably, the titanium source comprises a waste liquid containing titanium tetrachloride; Taking the total weight of the waste liquid containing titanium tetrachloride as 100%, the waste liquid containing titanium tetrachloride comprises: 80%-95% titanium tetrachloride, 2%-5% alkoxy titanium complex, and the remainder is hydrocarbons, and the hydrocarbons include hexane and esters.

15. The catalytic cracking catalyst according to claim 1 or 7, wherein: The phosphorus source includes one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphoric acid, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate; Preferably, the phosphorus source includes one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, magnesium phosphate, aluminum phosphate, phosphorous acid, ammonium phosphite, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.

16. The catalytic cracking catalyst according to claim 1, wherein: In the catalyst component A and the catalyst component B, the aluminum source includes one or a combination of two or more of pseudo-boehmite, amorphous alumina, boehmite, aluminum nitrate, and aluminum chloride.

17. The catalytic cracking catalyst according to claim 1, wherein The catalyst component B also includes an inorganic oxide carrier, and the inorganic oxide carrier includes one or a combination of two or more of white carbon black, an alumina material containing a B acid center, and a silicon-aluminum material containing a B acid center; Preferably, the weight of the inorganic oxide support material calculated as oxide is 0-30% of the weight of the catalyst B component.

18. The catalytic cracking catalyst according to any one of claims 1-2 and 11-17, wherein the raw material of the catalyst component B comprises 20%-45% of Y-type molecular sieve on a dry basis, based on 100% by weight of the raw material of the catalyst component B.

19. A method for preparing the catalytic cracking catalyst according to any one of claims 1 to 18, comprising: Preparation of catalyst component A: Modified ZSM-5 molecular sieve, clay, aluminum source and second modifier are mixed and slurried to form a first slurry; The first slurry is spray dried and calcined to obtain the catalyst component A; wherein the second modifier includes a phosphorus source; Preparation of catalyst component B: mixing Y-type molecular sieve, clay, aluminum source, binder and third modifier, and beating to form a second slurry; spray drying and calcining the second slurry to obtain the catalyst component B; the third modifier includes a modified metal source; The catalyst A component and the catalyst B component are mixed to obtain the catalytic cracking catalyst.

20. The method for preparing a catalytic cracking catalyst according to claim 19, wherein: The raw material of the catalytic cracking catalyst includes a pore structure improver, which is added to the first slurry and the second slurry, and the mass of the pore structure improver is 0.1%-10% of the total mass of the catalytic cracking catalyst; Preferably, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.

21. Use of the catalytic cracking catalyst according to any one of claims 1 to 18 in a catalytic cracking process.

Citation Information

Patent Citations

  • Catalytic thermal cracking catalyst and preparation method thereof

    CN101898146B

  • Method for improving B acid content of ZSM-5 molecular sieve and realizing yield increase of light olefin

    CN102114429B

  • Propylene polymerization catalyst

    CN102336851A

  • A polypropylene catalyst component, preparation method and catalyst thereof

    CN107434832B

  • Olefinic polymeric carrier catalyst system and preparation method thereof

    CN1110281A

Cited By

  • Catalyst for catalytic cracking and preparation method and application thereof

    CN121244275A